# Solve for a -(6-5a)-(20+4a)-11=-(4-6a)+(-a)+3

-(6-5a)-(20+4a)-11=-(4-6a)+(-a)+3
Simplify -(6-5a)-(20+4a)-11.
Simplify each term.
Apply the distributive property.
-1⋅6-(-5a)-(20+4a)-11=-(4-6a)-a+3
Multiply -1 by 6.
-6-(-5a)-(20+4a)-11=-(4-6a)-a+3
Multiply -5 by -1.
-6+5a-(20+4a)-11=-(4-6a)-a+3
Apply the distributive property.
-6+5a-1⋅20-(4a)-11=-(4-6a)-a+3
Multiply -1 by 20.
-6+5a-20-(4a)-11=-(4-6a)-a+3
Multiply 4 by -1.
-6+5a-20-4a-11=-(4-6a)-a+3
-6+5a-20-4a-11=-(4-6a)-a+3
Subtract 20 from -6.
5a-26-4a-11=-(4-6a)-a+3
Subtract 4a from 5a.
a-26-11=-(4-6a)-a+3
Subtract 11 from -26.
a-37=-(4-6a)-a+3
a-37=-(4-6a)-a+3
a-37=-(4-6a)-a+3
Simplify -(4-6a)-a+3.
Simplify each term.
Apply the distributive property.
a-37=-1⋅4-(-6a)-a+3
Multiply -1 by 4.
a-37=-4-(-6a)-a+3
Multiply -6 by -1.
a-37=-4+6a-a+3
a-37=-4+6a-a+3
a-37=6a-a-1
Subtract a from 6a.
a-37=5a-1
a-37=5a-1
a-37=5a-1
Move all terms containing a to the left side of the equation.
Subtract 5a from both sides of the equation.
a-37-5a=-1
Subtract 5a from a.
-4a-37=-1
-4a-37=-1
Move all terms not containing a to the right side of the equation.
Add 37 to both sides of the equation.
-4a=-1+37
-4a=36
-4a=36
Divide each term by -4 and simplify.
Divide each term in -4a=36 by -4.
-4a-4=36-4
Cancel the common factor of -4.
Cancel the common factor.
-4a-4=36-4
Divide a by 1.
a=36-4
a=36-4
Divide 36 by -4.
a=-9
a=-9
Solve for a -(6-5a)-(20+4a)-11=-(4-6a)+(-a)+3

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top